Case of paraneoplastic pemphigus with immunoglobulin (Ig)G and IgA antibodies to various antigens. Issue 8 (11th March 2016) - Otsuka, Yohei; Ueno, Takashi; Yamase, Aya; Ito, Michiko; Osada, Shinichi; Kawana, Seiji; Funasaka, Yoko; Teye, Kwesi; Ishii, Norito; Hashimoto, Takashi; Saeki, Hidehisa
Abstract: A 63‐year‐old Japanese man with non‐Hodgkin B‐cell lymphoma presented with erythematous skin lesions on his entire body, with oral, ocular and anal mucosal lesions. The patient was diagnosed with paraneoplastic pemphigus. Immunofluorescence showed both immunoglobulin (Ig)G and IgA antibodies to keratinocyte cell surfaces. Various immunoblot and enzyme‐linked immunosorbent assays showed both IgG and IgA antibodies to various autoantigens, including desmogleins, desmocollins, envoplakin, periplakin and bullous pemphigoid antigens. This was a unique case with a very rare autoantibody profile in paraneoplastic pemphigus.